Landscape, memory and history : anthropological perspectives - Stewart, Pamela J.; Strathern, Andrew (Anthropology, culture, and society., 2003)
"How do people perceive the land around them, and how is that perception changed by history? This book explores this question from an anthropological angle, assessing the connections between place, space, identity, nationalism, history and memory in a variety of different settings around the world. Taking historical change and memory as key themes, it is a broad study that will appeal to a readership across the social sciences. Contributors from North America, Australia, New Zealand, Taiwan, and Europe explore a wide variety of case studies that includes seascapes in Jamaica; the Solomon Islands; the forests of Madagascar; Aboriginal and European notions of landscape in Australia; place and identity in 19th century maps and the bogs of Ireland; contemporary concerns over changing landscapes in Papua New Guinea; and representations of landscape and history in the poetry of the Scottish Borders."--